The FKBP5 polymorphism rs1360780 influences the effect of an algorithm-based antidepressant treatment and is associated with remission in patients with major depression. (January 2016) - Stamm, Thomas J; Rampp, Carina; Wiethoff, Katja; Stingl, Julia; Mössner, Rainald; O′Malley, Grace; Ricken, Roland; Seemüller, Florian; Keck, Martin; Fisher, Robert; Gaebel, Wolfgang; Maier, Wolfgang; et al.
Objective: The FKBP5-gene influences the HPA-system by modulating the sensitivity of the glucocorticoid receptor (GR). The polymorphism rs1360780 has been associated with response in studies with heterogeneous antidepressant treatment. In contrast, several antidepressant studies with standardized antidepressant treatment could not detect this effect. We therefore compared patients with standardized vs naturalistic antidepressant treatment to (a) investigate a possible interaction between FKBP5-genotype and treatment mode and (b) replicate the effect of the FKBP5-genotype on antidepressant treatment outcome. Methods: A total of 298 major depressive disorder (MDD) inpatients from the multicentred German project and the Zurich Algorithm Project were genotyped for their FKBP5 status. Patients were treated as usual ( n =127) or according to a standardized algorithm ( n =171). Main outcome criteria was remission (Hamilton Depression Rating Scale-21<10). Results: We detected an interaction of treatment as usual (TAU) treatment and C-allele with the worst outcome for patients combining those two factors (HR=0.46; p =0.000). Even though C-allele patients did better when treated in the structured, stepwise treatment algorithm (SSTR) group, we still could confirm the influence of the FKBP5-genotype in the whole sample (HR=0.52; p =0.01). Conclusions: This is the first study to show an interaction between a genetic polymorphism and treatment mode. Patients with the C-allele of the rs1360780 polymorphism seem to benefit from a standardized antidepressant treatment.